2020
DOI: 10.1002/jbm.a.37023
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and in vitro evaluation of 3D composite scaffold based on collagen/hyaluronic acid sponge and electrospun polycaprolactone nanofibers for peripheral nerve regeneration

Abstract: Replacement of peripheral nerve autografts with tissue engineered nerve grafts will potentially resolve the lack of nerve tissue especially in patients with severe concomitant soft tissue injuries. This study attempted to fabricate a tissue engineered nerve graft composed of electrospun PCL conduit filled with collagen‐hyaluronic acid (COL‐HA) sponge with different COL‐HA weight ratios including 100:0, 98:2, 95:5 and 90:10. The effect of HA addition on the sponge porosity, mechanical properties, water absorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 58 publications
0
31
0
Order By: Relevance
“…Electrospinning is a multi-purpose and cost-effective process for producing non-woven micro/nanofibers, which can provide an excellent ECM-like environment for tissue and cell growth [ 57 , 58 ]. Electrospun fibers can meet various structural requirements for tissue engineering scaffolds, such as porosity, pores that communicate with each other, adjustable void size, functional filaments, and adjustable morphology [ 59 , 60 , 61 ].…”
Section: Conduit Spatial Structure and Fillersmentioning
confidence: 99%
“…Electrospinning is a multi-purpose and cost-effective process for producing non-woven micro/nanofibers, which can provide an excellent ECM-like environment for tissue and cell growth [ 57 , 58 ]. Electrospun fibers can meet various structural requirements for tissue engineering scaffolds, such as porosity, pores that communicate with each other, adjustable void size, functional filaments, and adjustable morphology [ 59 , 60 , 61 ].…”
Section: Conduit Spatial Structure and Fillersmentioning
confidence: 99%
“…Mechanical properties and degradation of HA can be tuned through chemical and physical processes of crosslinking with divinyl sulfone followed by freezing and lyophilization to create a porous structure (Ortuno-Lizarán et al, 2016;Vilariño-Feltrer et al, 2016). Moreover, HA can be solved with sodium chloride and directly poured into a porous sponge (Li et al, 2018;Entekhabi et al, 2020) or suspended in physiological saline solution to obtain a suitable viscosity useful to produce hydrogel fillers for NGCs (Li et al, 2018).…”
Section: Hyaluronic Acidmentioning
confidence: 99%
“…Although progress has been made in tissue engineering and regenerative medicine, and it has been observed that HA and collagen-based composite nanofibers show the greatest vascularization and tissue regeneration in vivo, the regenerative biochemical cascade behind them has not been further explored [ 17 19 ]. Controlling the interaction between macrophages and biomaterials is very important to promote tissue regeneration in regenerative medicine.…”
Section: Introductionmentioning
confidence: 99%